Bovine CNS Myelin Contains Neurite Growth-Inhibitory Activity Associated with Chondroitin Sulfate Proteoglycans - Niederöst, Barbara P. (J Neurosci, 1999)
The absence of fiber regrowth in the injured mammalian CNS is influenced by several different factors and mechanisms. Besides the nonconducive properties of the glial scar tissue that forms around the lesion site, individual molecules present in CNS myelin and expressed by oligodendrocytes, such as NI-35/NI-250, bNI-220, and myelin-associated glycoprotein (MAG), have been isolated and shown to inhibit axonal growth. Here, we report an additional neurite growth-inhibitory activity purified from bovine spinal cord myelin that is not related to bNI-220 or MAG. This activity can be ascribed to the presence of two chondroitin sulfate proteoglycans (CSPGs), brevican and the brain-specific versican V2 splice variant. Neurite outgrowth of neonatal cerebellar granule cells and of dorsal root ganglion neuronsin vitro was strongly inhibited by this myelin fraction enriched in CSPGs. Immunohistochemical staining revealed that brevican and versican V2 are present on the surfaces of differentiated oligodendrocytes. We provide evidence that treatment of oligodendrocytes with the proteoglycan synthesis inhibitors β-xylosides can strongly influence the growth permissiveness of oligodendrocytes. β-Xylosides abolished cell surface presentation of brevican and versican V2 and reversed growth cone collapse in encounters with oligodendrocytes as demonstrated by time-lapse video microscopy. Instead, growth cones were able to grow along or even into the processes of oligodendrocytes. Our results strongly suggest that brevican and versican V2 are additional components of CNS myelin that contribute to its nonpermissive substrate properties for axonal growth. Expression of these CSPGs on oligodendrocytes may indicate that they participate in the restriction of structural plasticity and regeneration in the adult CNS.